The Impact of Voice Behavior on Team Performance Evidence From Indonesian Retail Firms - Devi Alpiani; Deti Mulyo Harsono (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to investigate the impact of voice behavior on team performance in Indonesian retail companies. Voice behavior refers to the discretionary communication of ideas, suggestions, concerns, or opinions with the intent to improve organizational or team functioning. Given the dynamic and competitive nature of the retail industry, especially in developing economies like Indonesia, enhancing team performance has become a critical concern for organizational success. This research employed a quantitative method with a purposive sampling technique, involving 99 retail employees from various companies across Indonesia. The data collection was conducted through a structured questionnaire, and the analysis was carried out using Statistical Package for the Social Sciences (SPSS) version 22. The results of the analysis revealed that voice behavior has a positive and significant impact on team performance. This means that when employees are encouraged to speak up and actively participate in communication within the team, overall team performance improves. The study highlights the importance of creating an open communication climate and fostering a culture where employees feel psychologically safe to express their opinions and contribute to team discussions. These findings can serve as a reference for managers and HR practitioners in Indonesian retail companies to design policies and practices that support voice behavior. By encouraging open dialogue and inclusive decision-making, companies can enhance collaboration, innovation, and ultimately team productivity. This study also emphasizes the strategic role of employee involvement and communication in achieving high-performing teams.